Clinicians' experiences in signposting an online mental health resource to expectant mothers: a qualitative study - Sofie Saxild; Philip Wilson; Sarah de Voss; Gritt Overbeck (BMC, 2023)
Abstract Background Poor maternal mental well-being and a lack of secure parent-infant attachment, have been identified as important factors associated with adverse mental health outcomes later in a child's life. Interventions designed to care for maternal mental well-being during pregnancy and early parenthood, are therefore likely to support healthy child development. Mentalization is a skill parents can practice, improving the emotional bond to the child, offering insights into their own and the child's mental states and potentially improving parental mental well-being. Most pregnant women in Denmark schedule antenatal consultations in general practice, potentially offering a solid platform to promote web-based interventions aiming to enhance mentalization skills. Signposting towards online resources has several advantages including high accessibility, ease of distribution and cost-effectiveness. We aimed to explore the attitudes and experiences of clinicians in general practice in signposting women towards a web-intervention to increase parental mentalization skills. Methods The intervention was offered to pregnant women at their primary preventive antenatal consultation in Danish general practice around week eight of pregnancy, and was designed to be incorporated into the following antenatal- and pediatric consultations until the child's second birthday. Semi-structured interviews about clinicians' experiences with signposting the intervention were conducted with 11 general practitioners (GP), three practice midwives (MW) and one practice nurse (NR). Results Clinicians wanted to enhance the focus on mental well-being in pregnancy and early childhood during preventive consultations. The main barriers to signposting the web-program were decreasing motivation over time, lack of financial viability and time limitations. Utilizing a psychoeducational web-intervention was generally accepted by clinicians, but ideally not carried out solely in general practice. Conclusion Signposting web-programs to improve parental mentalization skills can be welcomed by clinicians in general practice but need to be more tailored to suit the everyday workflow of the clinics. Addressing parental mentalization remains largely unchartered territory for pregnant women and clinicians alike, therefore training clinicians on the subject and its presentation should be offered. Trial registration The study is part of a larger project that has been approved by the Research Ethics Committee at the University of Copenhagen, Nov. 2019 (reference number 504-0111/19-5000).